Il volo del “Moscone”: Vincenzo Ragognetti giornalista tra Napoli e São Paulo - Rorato, Marcia (Kritik. Rivista di letteratura e critica culturale, 2024)
The flight of the “Moscone” to Brazil was a journey of a cultural model, identifiable in the Neapolitan literary journalism of the late nineteenth century. That of the “Moscone” inaugurated by the brilliant Italian journalist, Matilde Serao, in Il Mattino and followed by the Italian-Brazilian writer, Vincenzo Ragognetti, in Il Moscone, founded in São Paulo, in 1925. The influence suffered by Ragognetti, during his two-year stay in Naples, was evident in his relevant journalistic and literary activity in São Paulo. In addition to collaborating and directing newspapers and writing works in different genres, he created his own periodical, Il Moscone, which, for example of the Mosconi della Serao, reported with irony, vivacity and movement the social life of the Italian Borghese society in the Paulistan capital of the twenties and the middle of the last century.